Experimental Investigation of Flow Inside the Back-Sidewall Gaps of Centrifugal Pump and its Impact on Axial Thrust. Issue 1 (1st September 2022) - Zemanová, L; Rudolf, P; Zubík, P
Abstract: Despite the sidewall gaps of centrifugal pumps are tiny narrow spaces, the flow inside them can have a great impact on the flow field in the whole machine. Regardless of its influence, there is no full understanding of the flow in those regions. A theory exists for the simplified cylindrical cavity with a rotating disk, whose application to real hydraulic machines is questionable. To investigate the flow in the sidewall gaps of centrifugal pumps, a test rig including a real impeller has been built up. It enables observation of the flow in the back-sidewall gap by optical methods and evaluation of axial thrust and torque. The measurements were performed for a range of rotational speeds in order to map possible flow regimes and patterns. It was found out, that the basic theory and map of the flow regimes obtained for a simple rotating cavity is inapplicable for the back-sidewall gaps of real hydraulic machines. The flow field is significantly influenced by the impeller blades, and consequently, the map of the regimes is shifted compared to the one derived for the simple cylindrical cavity with a rotating disk. The discrepancies were described and a new map of flow regimes was introduced.